Education and development in Asia and the Pacific. - Asian Development Bank. (Manila Asian Development Bank, 1988)
"The general aim of this paper is to determine the direction of the [Asian Development] Bank's future policy in assisting education. To this end, three steps are undertaken, reflected in the three chapters of the paper, each of them with specific objectives: (i) Chapter I provides a background analysis relevant to the education sector and development assistance in the region. Firstly, it describes the regional setting; and secondly, it analyzes the relationship between development and education; (ii) Chapter II has two objectives: a review of the present status of and on-going development trends in education in the region; and the analysis of key issues and tasks ahead. The chapter is meant both as an inventory and an analytical framework for decision makers from DMCs as well as from development assistance agencies, particularly the Bank; (iii) Chapter III, finally, has three objectives: a review of the Bank's past policy and performance in assisting education development in the region; a brief overview on other agencies? regional external assistance operations in the sector; and an outline of the Bank's future sectoral assistance policies and priorities."--Introduction.
Introduction -- Chapter I. Background to the education sector -- A. The regional setting -- B. Development and education -- Chapter II. The state of education development in the region -- A. Review of present status and development trends -- B. Key issues and tasks ahead -- Chapter III. The Bank's role in assisting education development -- A. The Bank's past policy and performance -- B. External assistance to the sector by other agencies -- C. The Bank's future assistance policies and priorities -- Annexes.
Keywords: Education -- Asia; Education -- Pacific area